2011
DOI: 10.1007/s10751-011-0542-y
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of ΛΛ hypernuclear events

Abstract: Highlights of ΛΛ emulsion events are briefly reviewed. Given three accepted events, shell-model predictions based on p-shell Λ hypernuclear spectroscopic studies are shown to reproduce B ΛΛ (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…On the other hand, still little is known about the hyperon-hyperon interaction resulting from the limited knowledge of double-Λ hypernuclei [56,57]. The few experimental data point towards a weakly attractive U Λ Λ potential [57][58][59]. Nothing can be said about ΛΞ and ΞΞ interactions.…”
Section: B Nucleon-hyperon Interactionmentioning
confidence: 99%
“…On the other hand, still little is known about the hyperon-hyperon interaction resulting from the limited knowledge of double-Λ hypernuclei [56,57]. The few experimental data point towards a weakly attractive U Λ Λ potential [57][58][59]. Nothing can be said about ΛΞ and ΞΞ interactions.…”
Section: B Nucleon-hyperon Interactionmentioning
confidence: 99%
“…The situation is more complicated for some of the 3-body or 4-body systems made of nucleons and hyperons, and needs to be clarified. The tetraneutron, 4 n = (n, n, n, n), is naively suggested by the stability of 8 He isotope, but has received only controversial experimental indications [1]. Its stability cannot be established using realistic neutron-neutron potentials [2][3][4][5][6], nor even with potentials made artificially deeper to produce a dineutron 2 n, due to the Pauli principle.…”
Section: Introductionmentioning
confidence: 99%
“…The physics of hypernuclei is progressing dramatically in both experiment and theory, for which recent reviews can be found in [7,8]. For baryon number A = 2, there is no evidence for a stable (n, Λ) nor (p, Λ) bound state, except for a mass peak of about 2.06 GeV seen in d + π − [9].…”
Section: Introductionmentioning
confidence: 99%
“…There have been significant progresses in the study of hypernuclei in both experiment and theory during the past decades. The discovery of a number of hypernuclei with S = −1 and S = −2 has greatly enriched our knowledge about the hyperon-nucleon and hyperon-hyperon interactions [254,255], and the search for stable hypernuclei still serves as a direct probe for many interesting physics with the presence of hyperons in nuclear matter.…”
Section: Search For New Dibaryons At the Nica Spd Facilitymentioning
confidence: 99%